The little prince - d; Howard, Richard, 1929-2022. (San Diego : Harcourt, 2000)
An aviator whose plane is forced down in the Sahara Desert encounters a little prince from a small planet who relates his adventures in seeking the secret of what is important in life.
Keywords: Fairy tales